2004
DOI: 10.1002/chp.1340240407
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of problem-based versus didactic seminars for disseminating evidence-based guidelines on asthma management to primary care physicians

Abstract: PBL was as effective in knowledge uptake and retention as lecture-based continuing medical education (CME) programs. Further study is warranted to investigate whether the assessment of higher educational value or an increase in response rate to delayed testing is replicable in other RCTs addressing common confounders and if these factors influence future CME participation, changes in physician clinical behavior, or patient health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 7 publications
5
30
0
Order By: Relevance
“…33 The positive feedback received particularly for the interactive style of teaching is consistent with the results of other studies which show that interactive discussions are more popular with students and teachers than more didactic approaches. 34,35 Previous studies have also shown that student motivation is also heightened by an interactive style of teaching [36][37][38] which might explain some of the student's perceived attitude changes regarding psychiatry and also their enthusiasm for psychiatry following the course.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…33 The positive feedback received particularly for the interactive style of teaching is consistent with the results of other studies which show that interactive discussions are more popular with students and teachers than more didactic approaches. 34,35 Previous studies have also shown that student motivation is also heightened by an interactive style of teaching [36][37][38] which might explain some of the student's perceived attitude changes regarding psychiatry and also their enthusiasm for psychiatry following the course.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…While typically there is no significant difference in academic achievement between PBL and traditional students (Albanese and Mitchell, 1993;White et al, 2004), research indicates that students develop an improved attitude towards learning and higher level thinking skills when PBL is used -for example, critical analysis, problem solving and reflection (Heliker, 1994). Spronken-Smith (2005) reported that students perceived greater development of problem-solving and analytical skills following a PBL module in research methods.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have argued that various alternative teaching methods are superior to lectures, [68][69][70] many studies have demonstrated that these alternatives are merely equivalent or perhaps even inferior to didactic teaching. [71][72][73][74][75][76][77][78][79][80] Some educators believe that lectures by experts in specific areas of medicine may still have value, although some limited data suggest that expert guest speakers at grand rounds do not produce increased knowledge retention. 81 What Strategies Are Available to Enhance Didactic Learning Sessions Within EM Programs and How Should Their Success Be Measured?…”
Section: Consensus Statement On Simulation-based Medicalmentioning
confidence: 99%